Экстраполяция функции комплексной ошибки систем автоматического управления с обратной связью - Агамалов, О.Н. (Технічна електродинаміка, 2012)
In the report the new type of a feedback based on structure and the subsequent extrapolation of a complex error function (CEF) of control systems is considered. Defining Hilbert's transform any an input and output of control system in the form of analytical signals, there is an instant phase delay between them and structure of CEF. Further, having defined CEF as not analytical complex function of complex argument (an output of plant) in an equilibrium point (the steady-state mode) and using a Wirtinger derivative for calculation of gains a power series, CEF it is extrapolated in an equilibrium point of control system at change of an output of plant. Extrapolated (predicted) value of CEF is used in a contour of feedback of control system.